2015
DOI: 10.1007/s00289-015-1382-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry: a novel approach to graft polypropylene with dual monomers (PP-g-(MAH-co-St))

Abstract: Mechanochemistry as an energy-saving and highly efficient synthetic method emerges great potential in various chemical syntheses. The multi-phase compatibilizer polypropylene (PP) grafted with maleic anhydride (MAH) and styrene (St) (PP-g-(MAH-co-St)) was successfully obtained by mechanochemical method without any solvent within minutes. The PP-g-(MAH-co-St) with G MAH = 0.24-1.40 % were made by mechanochemistry successfully. The impact of monomers concentration, initiator concentrations, particle size of PP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…(swell condition: 37°C, 3 h and 8.5 MPa; grafting reaction condition: 80°C and 8 h; w monomer :w PP = 30 wt%; other conditions were the same as those in Fig. 2) capture radicals on the HPP backbone as rapidly as possible [24]. Therefore, PETA could be significantly improved in the presence of St.…”
Section: Resultsmentioning
confidence: 94%
“…(swell condition: 37°C, 3 h and 8.5 MPa; grafting reaction condition: 80°C and 8 h; w monomer :w PP = 30 wt%; other conditions were the same as those in Fig. 2) capture radicals on the HPP backbone as rapidly as possible [24]. Therefore, PETA could be significantly improved in the presence of St.…”
Section: Resultsmentioning
confidence: 94%
“…The spectrum showed a weak peak intensity due to aromatic protons in the range of 6.9–7.4 ppm and characteristic peaks due to the succinyl functional groups of MAH in the range of 2–3 ppm, respectively. [ 50 , 51 ] DSC thermal study also showed that the thermal parameters such as crystallization and melting temperature of PLA decrease after MAH and St/MAH grafting, indicating that the crystallization of PLA was limited to steric hindrance of the grafted pendant [ 52 , 53 ] (Figure S3 , Supporting Information). Figure S4 , Supporting Information, shows that the compositional ratio of ST to MAH strongly influenced the grafting efficiency and the melt flow index (MFI) of PLA upon the MAH grafting process.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the maximum values of GP and AV are appeared around St/MA: 70/30. Because of the low polymerization capability, MA units tend to graft either directly onto a PVC chain or onto the St radicals that have already been grafted on PVC chain . As the potential of St monomers to polymerize is higher than that of MA, therefore those can be grafted directly onto the other St radicals, as well as on PVC chains or grafted MA .…”
Section: Resultsmentioning
confidence: 99%
“…The observed trend is usual for graft copolymerization reactions via chain transfer. The higher concentration of the initial radicals leads to the higher chain transfer to the polymer backbone . However, the copolymerization between MA and St is increased by excessive concentration of the initiator, which tends to terminate the grafting reaction, and as a result, GP and AV values will be dropped.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation